Brain morphometric abnormalities in boys with attention‐deficit/hyperactivity disorder revealed by sulcal pits‐based analyses. (6th August 2020) - Li, Xin‐Wei; Jiang, Yu‐Hao; Wang, Wei; Liu, Xiao‐Xue; Li, Zhang‐Yong
Abstract: Aim: Attention‐deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder associated with widespread brain morphological abnormalities. Here, we utilized a sulcal pits‐based method to provide new insight into the atypical cortical folding morphology in ADHD. Methods: Sulcal pits, the locally deepest points in each fold, were first extracted from magnetic resonance imaging data of 183 boys with ADHD (10.62 ± 1.96 years) and 167 age‐ and gender‐matched typically developing controls (10.70 ± 1.73 years). Then, the geometrical properties of sulcal pits were statistically compared between ADHD and controls. Results: Our results demonstrated that the number of sulcal pits was reduced and confined to the superficial secondary sulci in the ADHD group relative to controls ( P < .05). We also found that ADHD boys were associated with significantly increased pit depth in the left superior frontal junction, circular insular sulcus, right inferior frontal junction, and bilateral cingulate sulcus, as well as significantly decreased pit depth in the bilateral orbital sulcus ( P < .05, corrected). Conclusion: The experimental findings reveal atypical sulcal anatomy in boys with ADHD and support the feasibility of sulcal pits as anatomic landmarks for disease diagnosis. Abstract : Sulcal pits analysis revealed decreased pits number in superficial secondary sulci and abnormal pit depth in multiple brain regions in boys with ADHD, providing new insights into this disease.